Input subsidy programs in sub-Saharan Africa: A synthesis of recent evidence - Jayne, Thomas S.; Rashid, Shahidur (Wiley, 2013)
Input subsidy programs have once again become a major plank of agricultural development strategies in Africa. Ten African governments spend roughly US$1 billion annually on input subsidy programs (ISPs), amounting to 28.6% of their public expenditures on agriculture. This article reviews the microlevel evidence on ISPs undertaken since the mid 2000s. We examine the characteristics of subsidy beneficiaries, crop response rates to fertilizer application and their influence on the performance of subsidy programs, the impacts of subsidy programs on national fertilizer use and the development of commercial input distribution systems, and finally the impact of ISPs on food price levels and poverty rates. The weight of the evidence indicates that the costs of the programs generally outweigh their benefits. Findings from other developing areas with a higher proportion of crop area under irrigation and with lower fertilizer prices—factors that should provide higher returns to fertilizer subsidies than in Africa—indicate that at least a partial reallocation of expenditures from fertilizer subsidies to R&D and infrastructure would provide higher returns to agricultural growth and poverty reduction. However, because ISPs enable governments to demonstrate tangible support to constituents, they are likely to remain on the African landscape for the foreseeable future. Hence, the study identifies ways in which benefits can be enhanced through changes in implementation modalities and complementary investments within a holistic agricultural intensification strategy. Among the most important of these are efforts to reduce the crowding out of commercial fertilizer distribution systems and programs to improve soil fertility to enable farmers to use fertilizer more efficiently. The challenges associated with achieving these gains are likely to be formidable.